Thy Sea is Great, Our Boats are Small, and Other Hymns of To-Day - Van Dyke, Henry, 1852-1933 (Salt Lake City, UT : Project Gutenberg, 2013)
"Thy Sea is Great, Our Boats are Small, and Other Hymns of To-Day" by Henry Van Dyke is a collection of hymns penned in the early 20th century. The book expresses contemporary Christian sentiments and explores themes of trust, joy, and hope amidst the challenges of the modern world. The work aims to create a bridge between faith and the realities of life, encouraging readers to find solace and strength in their beliefs. The collection features several hymns, each reflecting a different aspect of faith and spirituality. Van Dyke$1 (Bs verses weave imagery of the sea and the human experience, inviting readers to trust in God$1 (Bs presence during life's voyages. He addresses the struggles of labor, the importance of unity in Christ, and the search for peace in a tumultuous world. Throughout the hymns, there is an emphasis on the divine qualities of love, guidance, and renewal, underscoring the idea that true victory and joy lie within. The simplicity and earnestness of the hymns make them accessible, reflecting the profound yearning of the heart for connection with the divine. (This is an automatically generated summary.)s
Release date is 2013-07-05
Produced by Stephen Hutcheson
Keywords: Hymns